Simvastatin Radiosensitizes Differentiated and Stem-Like Breast Cancer Cell Lines and Is Associated With Improved Local Control in Inflammatory Breast Cancer Patients Treated With Postmastectomy Radiation. (15th May 2014) - Lacerda, Lara; Reddy, Jay P.; Liu, Diane; Larson, Richard; Li, Li; Masuda, Hiroko; Brewer, Takae; Debeb, Bisrat G.; Xu, Wei; Hortobágyi, Gabriel N.; Buchholz, Thomas A.; Ueno, Naoto T.; et al.
Abstract : The authors studied the radiosensitization of breast cancer stem-like cells in vitro after treatment with the most commonly used statin, simvastatin, and examined the influence on local control after postmastectomy radiation among inflammatory breast cancer patients taking statins. This work provides new insight on combination regimens for breast cancer treatment and radiosensitization of this clinically radioresistant disease. Abstract: : Reported rates of local failure after adjuvant radiation for women with inflammatory breast cancer (IBC) and triple-negative non-IBC are higher than those of women with receptor-expressing non-IBC. These high rates of locoregional recurrence are potentially influenced by the contribution of radioresistant cancer stem cells to these cancers. Statins have been shown to target stem cells and improve disease-free survival among IBC patients. We examined simvastatin radiosensitization of multiple subtypes of breast cancer cell lines in vitro in monolayer and mammosphere-based clonogenic assays and examined the therapeutic benefit of statin use on local control after postmastectomy radiation (PMRT) among IBC patients. We found that simvastatin radiosensitizes mammosphere-initiating cells (MICs) of IBC cell lines (MDA-IBC3, SUM149, SUM190) and of the metaplastic, non-IBC triple-negative receptor cell line (SUM159). However, simvastatin radioprotects MICs of non-IBC cell lines MCF-7 and SKBR3. In a retrospective clinical study of 519 IBC patients treated with PMRT, 53 patients used a statin. On univariate analysis, actuarial 3-year local recurrence-free survival (LRFS) was higher among statin users, and on multivariate analysis, triple negative breast cancer, absence of lymphatic invasion, neoadjuvant pathological tumor response to preoperative chemotherapy, and statin use were independently associated with higher LRFS. In conclusion, patients with IBC and triple-negative non-IBC breast cancer have the highest rates of local failure, and there are no available known radiosensitizers. We report significant improvement in local control after PMRT among statin users with IBC and significant radiosensitization across triple-negative and IBC cell lines of multiple subtypes using simvastatin. These data suggest that simvastatin should be justified as a radiosensitizing agent by a prospective clinical trial.